PENGEMBANGAN LAHAN BASAH SUB-OPTIMAL: KESESUAIAN LAHAN TANAMAN KELOR (Moringa oleifera) PADA TANAH SULFAT MASAM BARITO KUALA KALIMANTAN SELATAN - Rabiatul Wahdah; Anna Maria Makalew (Jurnal Hutan Tropis, 2022)
Moringa is a plant that has a many of benefits both for fulfilling human nutrition and as an ingredient used for animal feed. Information to the public is still very minimal about the benefits of this Moringa plant, and it is also needed to expand the land to cultivate it. Acid sulphate land is an rarely used land for agricultural crop cultivation because it has a serious limiting factor, but has the potential to be planted with Moringa plant, because Moringa plant tolerance to high acidity. For the business certainty, it is need to be evaluation the land suitability of Moringa plant in acid sulphate land as the use of wetland is not optimal. This research was conducted in Barito Kuala, Tabukan sub-district for the first year. This research uses a survey method by taking several soil samples with purposive sampling which is then analyzed in the laboratory, then interpreted whether it is suitable for Moringa plant so that it can be recommended and socialized to the public for cultivated in acid sulphate tidal land. From the aspect of human resources and land availability, the prospect of developing Moringa plant in Tabukan sub-district is still possible, but in terms of suitability and soil quality, in-depth studies are still needed.